Australian Sea Snake Envenoming Causes Myotoxicity and Non-Specific Systemic Symptoms - Australian Snakebite Project (ASP-24) - Johnston, Christopher I.; Tasoulis, Theo; Isbister, Geoffrey K. (Frontiers in Pharmacology, 2022)
Background: Sea snakes are venomous snakes found in the warm parts of the Indo-Pacific, including around Australia. Most sea snake envenoming causes myotoxicity, but previous Australian case reports describe neurotoxicity. We aimed to describe the epidemiology and clinical presentation of Australian sea snake envenoming and the effectiveness of antivenom. Methods: Patients were recruited to the Australian Snakebite Project (ASP), an Australia-wide prospective observational study recruiting all patients with suspected or confirmed snakebite >2 years. Information about demographics, bite circumstances, species involved, clinical and laboratory features of envenoming, and treatment is collected and entered into a purpose-built database. Results: Between January 2002 and August 2020, 13 patients with suspected sea snake bite were recruited to ASP, 11 were male; median age was 30 years. Bites occurred in Queensland and Western Australia. All patients were in or around, coastal waters at the time of bite. The species involved was identified in two cases (both Hydrophis zweifeli). Local effects occurred in 9 patients: pain (5), swelling (5), bleeding (2), bruising (1). Envenoming occurred in eight patients and was characterised by non-specific systemic features (6) and myotoxicity (2). Myotoxicity was severe (peak CK 28200 and 48100 U/L) and rapid in onset (time to peak CK 13.5 and 15.1 h) in these two patients. Non-specific systemic features included nausea (6), headache (6), abdominal pain (3), and diaphoresis (2). Leukocytosis, neutrophilia, and lymphopenia occurred in both patients with myotoxicity and was evident on the first blood test. No patients developed neurotoxicity or coagulopathy. Early Seqirus antivenom therapy was associated with a lower peak creatine kinase. Conclusion: While relatively rare, sea snake envenoming is associated with significant morbidity and risk of mortality. Early antivenom appears to have a role in preventing severe myotoxicity and should be a goal of therapy.